Pemberdayaan Kelompok Petani Argowisata Banda Lonthoir Melalui Pelatihan Pembuatan Eco-enzyme Berbahan Dasar Limbah Kulit Pala - Juen Carla Warella; Melda Yunita; Eka Astuti; Merry Patteilohy; Kezia Josawel Lesbatta (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Organic waste is a major environmental and societal concern. This waste originates from households, agricultural industries, and livestock. Piles of organic waste that are not managed properly will cause water, soil, and air pollution. Banda Lonthoir Village is one of the areas that has not implemented proper processing and utilization of organic waste. This is because Banda Lonthoir Village is the largest producer of nutmeg in Maluku. The nutmeg plants that are utilized are seeds and mace, whereas nutmeg skin is usually made into sweets, and most of it is thrown away as organic waste. One solution for processing organic waste from nutmeg skin is to use eco-enzymes. This activity aims to provide education and training in creating eco-enzymes to the community so that they can increase their knowledge on how to manage nutmeg skin waste. The method of implementing this activity is to provide materials and training processes for making eco-enzymes. The target of this activity is the Nutmeg Garden Agrotourism Farmers Group and the Banda Lonthoir Village apparatus. The results of this activity show that the community is very enthusiastic and participates in listening to the material and making eco-enzymes, as well as asking questions related to the activities provided. The community was able to make eco-enzymes according to the procedure explained and ferment 10 L of eco-enzyme. The community gave a positive response and had an impact on increasing community knowledge regarding how to manage nutmeg skin waste into eco-enzymes that are beneficial for the community and the environment.